Will Experiences of Doctoral Study in China influence African Academic Practice? - Robinson, Natasha; Mills, David (International Higher Education, 2022)
In the five years leading up to the COVID-19 pandemic, the number of African doctoral researchers training in China doubled to 8,000, often on scholarships funded by the Chinese government. Many plan to return to posts in African universities. Will these experiences influence African university research cultures, doctoral supervision, and publishing practices?